Outcomes of cesarean delivery in obstetric patients with SARS‐CoV‐2 infection. Issue 3 (22nd September 2021) - Lankford, Allison; Berger, Jeffrey; Benjenk, Ivy; Jackson, Amanda; Ahmadzia, Homa; Mazzeffi, Michael
Synopsis: SARS‐CoV‐2 infection was not associated with increased mortality, but was associated with a modest increase in morbidity, including stillbirth, in cesarean delivery patients in Maryland, USA.